2012
DOI: 10.1039/c2jm31748f
|View full text |Cite
|
Sign up to set email alerts
|

Cell and cell sheet recovery from pNIPAm coatings; motivation and history to present day approaches

Abstract: The regeneration of cells and cell sheets mediated by thermoresponsive substrates represents an important and ever growing area in tissue engineering. This review seeks to track the development of this field from inception to the present day by highlighting the most significant breakthroughs as well as focusing on important physical and chemical characterization of substrates produced for this specific purpose. Furthermore, a critical evaluation encompassing the advantages and disadvantages of different techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
77
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(80 citation statements)
references
References 70 publications
(102 reference statements)
2
77
0
Order By: Relevance
“…A number of different cell lines including 3T3 fibroblasts and hMSCs were successfully grown under standard physiological conditions and were subsequently gently detached upon temperature reduction. [10] Studies have shown that cells attach and therefore proliferate poorly on thick or bulk pNIPAm coatings and many studies report a coating thickness limitation above which there is a 4 dramatic reduction in the number of cells attaching to the polymer surface [12][13][14][15][16]. In studies where pNIPAm was covalently grafted for this purpose, this thickness limitation is in the order of tens of nanometers with the exception of coatings formed via plasma polymerization [12,[17][18][19].…”
Section: This Is Becoming Increasingly Desirable As the Regulatory Bimentioning
confidence: 99%
“…A number of different cell lines including 3T3 fibroblasts and hMSCs were successfully grown under standard physiological conditions and were subsequently gently detached upon temperature reduction. [10] Studies have shown that cells attach and therefore proliferate poorly on thick or bulk pNIPAm coatings and many studies report a coating thickness limitation above which there is a 4 dramatic reduction in the number of cells attaching to the polymer surface [12][13][14][15][16]. In studies where pNIPAm was covalently grafted for this purpose, this thickness limitation is in the order of tens of nanometers with the exception of coatings formed via plasma polymerization [12,[17][18][19].…”
Section: This Is Becoming Increasingly Desirable As the Regulatory Bimentioning
confidence: 99%
“…So far, various strategies have been described to covalently or non-covalently immobilize PNIPAM on surfaces for the generation of thermoresponsive cell culture substrates [1,14]. Among them is electron beam polymerization of N-isopropylacrylamide on polystyrene cell culture dishes [2,15].…”
Section: Introductionmentioning
confidence: 99%
“…A common practice for generating thermo-responsive surfaces for cell sheet engineering and therapeutic treatment for damaged tissues and organs is grafting thermo-responsive polymers, such as poly(N-isopropylacrylamide) (pNIPAAm), as brushes to a surface. [2][3][4]13 This approach could be more expensive and tedious as compared to the coupling/adhesion promoting approach. [2][3][4][5] However, the thermo-responsive and cellular behaviors on these retained pNIPAAm films as well as the mechanistic study of this coupling/adhesion promoting approach to retain these thermo-responsive polymers, to the best of our knowledge, have not been investigated.…”
Section: Introductionmentioning
confidence: 99%